2022
DOI: 10.1051/0004-6361/202142361
|View full text |Cite
|
Sign up to set email alerts
|

Euclid preparation

Abstract: We present a new infrared survey covering the three Euclid deep fields and four other Euclid calibration fields using Spitzer Space Telescope's Infrared Array Camera (IRAC). We combined these new observations with all relevant IRAC archival data of these fields in order to produce the deepest possible mosaics of these regions. In total, these observations represent nearly 11 % of the total Spitzer Space Telescope mission time. The resulting mosaics cover a total of approximately 71.5 deg 2 in the 3.6 and 4.5 µ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 32 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…The biggest difference in the photometric depth between our catalog and the COSMOS2020 is in the MIR bands, where IRAC-1 and IRAC-2 maps (Moneti et al 2022) are slightly deeper than the ones we used, as summarized in Table 3. We checked the MIR fluxes of the sources that we have in common with the COSMOS2020 catalog and verified that using the deeper IRAC maps would not change our results.…”
Section: Appendix a Comparison With Cosmos2020mentioning
confidence: 88%
See 1 more Smart Citation
“…The biggest difference in the photometric depth between our catalog and the COSMOS2020 is in the MIR bands, where IRAC-1 and IRAC-2 maps (Moneti et al 2022) are slightly deeper than the ones we used, as summarized in Table 3. We checked the MIR fluxes of the sources that we have in common with the COSMOS2020 catalog and verified that using the deeper IRAC maps would not change our results.…”
Section: Appendix a Comparison With Cosmos2020mentioning
confidence: 88%
“…15 This is the same UltraVISTA data release as used in the recent COSMOS2020 catalog (Weaver et al 2022). 16 The IRAC maps used in the COSMOS2020 catalog are instead those from Moneti et al (2022): the difference is minimal and only concerns channels 1 and 2, as shown in Figure 3 of Weaver et al (2022).…”
Section: Median Photometrymentioning
confidence: 99%
“…u-band observations are conducted by the MegaCam instrument at CFHT, and other optical bands (g, r, i, and z) are available from Subaru's HSC imaging. The Spitzer/IRAC channel 1, 2 (ch1, ch2) data are compiled from all the IRAC observations of the COSMOS field (Moneti et al 2022). Near-IR photometry in Y, J, and H bands are obtained from the UltraVISTA survey (McCracken et al 2012).…”
Section: Datamentioning
confidence: 99%
“…H20 will provide u-band observations from the MegaCam instrument on the Canada−France−Hawaii Telescope (CFHT) and g-, r-, i-, and z-band imaging from the Hyper Suprime-Cam (HSC) instrument on the Subaru Telescope over 20 deg 2 of the Euclid deep fields. Spitzer/IRAC observations from the Spitzer Legacy Survey (SLS) are also available in the same fields (Moneti et al 2022). In this paper, we identify the importance of wave bands for an H20+UVISTA-like survey with similar wavelength coverage expected in Euclid deep fields, incorporating the near-IR YJH bands from UltraVISTA (McCracken et al 2012) in addition to the H20 and SLS wave bands.…”
Section: Introductionmentioning
confidence: 99%
“…However, the forthcoming Euclid mission will open up a new era in the search of such objects by mapping a large area of the sky at NIR wavelengths. In addition to its main wide survey, Euclid will perform deep observations of three so-called Euclid Deep Fields, which will encompass a total area of ∼50 deg 2 Moneti et al 2022;McPartland et al, in prep). In the best-case scenario, Euclid Deep sources will have photometric coverage in at most 10-12 filters, and therefore deriving accurate photometric redshifts and galaxy physical parameters will be challenging.…”
Section: Introductionmentioning
confidence: 99%